Soberba nas relações humanas: implicações na atuação do psicólogo clínico - Vale, Cynthia Lopes do (2021)
The research originated from clinical observations on the psychologist's conduct when dealing with people's values, which organize their behavior and relationships. In this work, special attention is directed to pride, understood as a human value that is part of the human condition, having crossed periods, cultures, and spaces. Thus, the objective is to investigate the psychologist's pride characteristics in his clinical performance. For this, there was a contextualization of values in the light of Environmental Psychology, as well as it´s temporal, spatial and cultural dimensions. Then, pride was contextualized through philosophy, literature, cinema, and history, with a special focus on the teachings of Saint Thomas Aquinas about the Seven Capital Vices, as he was the last theorist to organize the studies carried out up to his time. This history indicated that pride was, initially, contextualized as an excess that, over time, came to be understood as an evil to be fought. However, this work analyzes pride as a human value through the autobiographical narrative of a clinical case. The described and analyzed parts of the case were chosen because they triggered the psychologist's pride in some way. The analysis was based on the cultural, temporal, and spatial dimensions of Environmental Psychology, in the line of research Contemporary Orientations in Clinical Psychology. The result suggested that pride can be understood as a value that strengthens and weakens the person and their relationships: it strengthens by establishing limits of the person to the world and weakens because it puts them in a situation of vulnerability, which can be understood as self-protection, capable to interfere in the psychologist's performance during the service. Therefore, pride should be expressed in a balanced way. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001